Devising a method for managing the configuration of products within an eco-logistics system project - Rudenko, Sergey; Kovtun, Tetiana; Smrkovska, Victoriya (Eastern-European Journal of Enterprise Technologies, 2022)
This paper considers the need to transform logistics systems into eco-logistics ones in order to achieve environmental goals of sustainable development. It was determined that one of the ways to reduce the eco-destructive impact of eco-logistics systems on the environment is the use of project management methodology tools and making changes to the project life cycle by including ecologically oriented phases. The products obtained during the life cycle of an eco-logistics system project have been identified and the links between the products of individual phases of the project have been established. The object of this study is the method of managing the configuration of products of the eco-logistics system project, which includes three stages: product parameter specification, product clustering, and structuring of the project’s product clusters. A description of each stage is provided. The specification of product parameters is to create descriptive frame models of products that contain the parameters necessary to characterize the product phase of the project, which are reflected in the content of the project’s products. Product clustering involves the creation of information models of product clusters that contain information about the set of products of the project phases that have close parameter values. Structuring clusters of project products leads to the creation of a network of clusters between which connections are formed, which makes it possible to build a product configuration. Experimental calculations confirming the adequacy of the application of the proposed method of managing the configuration of products of the eco-logistics system project are presented. As a result, a network of clusters of project products has been created, using which makes it possible to synthesize product chains that would have maximum value in terms of complying with eco-logistics rules and could minimize the negative impact on the environment.